2017
DOI: 10.1002/clen.201700548
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Potentially Toxic Elements in Cereal and Legume Crops: A Review

Abstract: Contamination of soil and water with potentially toxic elements (PTEs) has become a global environmental concern that could pose potential risks to human health and agriculture. The major anthropogenic sources of PTEs contamination include coal combustion processes, leather tanning operations, mining, smelting activities, and use of sewage water for irrigation. Scattered studies are available in the literature that determines the sources, bioavailability, and potential hazards due to PTEs contamination to crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 165 publications
(189 reference statements)
1
6
0
Order By: Relevance
“…In relation to PTE concentrations, microbial biomass results were negatively affected by soil Ni and V concentrations, as often reported in literature [66]. It is known that several PTEs such as Cu, Mn and Zn are essential for microbes and plants, and are essential in maintaining soil functionality, but they can be a threat when present in high concentrations [67,68]. In this context, enzyme activities are not only important in sustaining the bio-geochemical cycles, but are excellent ecological indicators of soil quality [69,70], being greatly affected by soil type and toxic pollutant characteristics (i.e., most of them are reduced greatly by high heavy metal contamination) [70][71][72][73].…”
Section: Discussionsupporting
confidence: 62%
“…In relation to PTE concentrations, microbial biomass results were negatively affected by soil Ni and V concentrations, as often reported in literature [66]. It is known that several PTEs such as Cu, Mn and Zn are essential for microbes and plants, and are essential in maintaining soil functionality, but they can be a threat when present in high concentrations [67,68]. In this context, enzyme activities are not only important in sustaining the bio-geochemical cycles, but are excellent ecological indicators of soil quality [69,70], being greatly affected by soil type and toxic pollutant characteristics (i.e., most of them are reduced greatly by high heavy metal contamination) [70][71][72][73].…”
Section: Discussionsupporting
confidence: 62%
“…Kumar et al [6] particularly underlined these chemical properties of FA, because it is composed of aluminium, iron, silicon and calcium oxides in 95-99% and the pH of FA usually ranges from 4.5 to 12.0 (in this study the pH of the FA was 13.7, see Table 1). Shahkolaie et al [9] and Murtaza et al [14] stressed the significance of the alkaline pH and the presence of sorption mineral colloids, such as Fe and Mn oxides, for increased Pb adsorption. Moreover, both the compost and FA resulted in an increase of Pb contents in soil compared to the control soil, which was the most pronounced in the exchangeable, water-and acid-soluble (Fr.…”
Section: Discussionmentioning
confidence: 99%
“…In this context the response of plants is particularly important, as they constitute an essential link in the food chain, into which metals can be incorporated. The effect of lead on morphological, physiological and biochemical processes in plants has been investigated by various authors [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Guo et al (2011) reported significant acidification of major Chinese croplands between the 1980s and the early 2000s, while Fang et al (2007) and Tang et al (2018) presented evidence of the impacts of human activities on carbon sequestration in China's soils and ecosystems. In addition, soil acidification has been reported on agricultural land and forest land in UK (Blake, 1999;Blake, 2002;Goulding, 2016), North America and Europe (Reuss et al, 1987), which have led to a potential risk of soil bioaccumulation in human and plants health (Murtaza et al, 2017). However, there is still a shortage of systematic information from which to evaluate the spatio-temporal ranges and variations in the pH and SOM of Chinese soils across different land uses.…”
Section: Introductionmentioning
confidence: 99%